Compositional Engineering of Chloride Ion‐Doped CsPbBr3 Halides for Highly Efficient and Stable All‐Inorganic Perovskite Solar Cells. Issue 10 (26th August 2020) - Li, Xueke; He, Benlin; Gong, Zekun; Zhu, Jingwei; Zhang, Wenyu; Chen, Haiyan; Duan, Yanyan; Tang, Qunwei
Abstract : Carbon‐based CsPbBr3 perovskite solar cells (PSCs) without hole‐transporting layers (HTLs) have aroused extensive attention due to their low manufacturing cost and prominent ambient stability. However, the defects of perovskite film and the poor charge extraction within PSCs result in severe charge recombination, which restricts the further enhancement of device efficiency. In view of this critical point, a compositional engineering of CsPbBr3 perovskite via doping with Cl − ions is presented herein to decrease the trap states and enhance the charge extraction. It is revealed that the doping of Cl − ions not only enlarges the grain size and thereby reduces the trap‐state density, but also optimizes the energy‐level alignment and improves the hole mobility of the perovskite film, leading to an evidently suppressed charge recombination and improved charge extraction and transportation. As a result, a champion power conversion efficiency (PCE) of 9.73% is achieved for carbon‐based HTL‐free CsPbBr2.98 Cl0.02 PSC, yielding a marked enhancement in comparison with 6.69% efficiency for the control. Meanwhile, the thermal and moisture stabilities of unencapsulated CsPbBr2.98 Cl0.02 PSC are improved, maintaining 93% and 95% of the initial PCE after expose to air atmosphere with 80% relative humidity (RH) and at 80 °C over 60 days, respectively. Abstract : A large‐grained CsPbBr3 perovskite film with improved energy‐level alignment and hole mobility is fabricated by compositional engineering of Cl ion doping, which suppresses charge recombination thus affording a champion power conversion efficiency (PCE) as high as 9.73% for carbon‐based all‐inorganic CsPbBr2.98 Cl0.02 PSC free of encapsulation with excellent operational stability.